Analysis of the Effectiveness of Marketing Strategies at Private Universities in Padang City - Habibah Muharmi; Rozi Destian; Windy Kusumahati; Fesaraweny Fesaraweny; Riko Erlima Putra (Sean Institute, 2026)
This study aims to analyze the effectiveness of a service marketing mix-based marketing strategy (7P Marketing Mix) on prospective students' decision-making at private universities in Padang City. The independent variables (X) consist of product, price, place, promotion, people, process , and physical evidence , while the dependent variable (Y) is decision-making. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to respondents who were students at several private universities in Padang City. Data analysis was conducted using multiple linear regression to determine the simultaneous and partial effects of each X variable on Y. The results showed that simultaneously, the seven dimensions of the marketing mix had a significant effect on decision-making. Partially, the promotion and physical evidence variables had the most dominant influence. These findings provide strategic implications for private universities to focus on improving the quality of promotions and physical evidence to strengthen the appeal and trust of prospective students.